P24 Examining screening test accuracy in Tyrosinemia type 1: A comparison of rapid and systematic review Methods. (13th September 2016) - Stinton, C; Taylor-Phillips, S; Geppert, J; Freeman, K; Johnson, S; Fraser, H; Sutcliffe, P; Clarke, A
Abstract : Background: Rapid reviews have received increasing interest in informing decision-making. However, the consequences of reducing the steps in the review process remain unclear. Questions remain about the degree of influence that individual components of a review have on its results and what the minimum elements are to ensure accuracy and reliability. We examined the impact that streamlining the review process had upon the results of a review of a newborn screening test for Tyrosinemia type 1 (TT1). Methods: Methods differed between the rapid- and systematic reviews. For the rapid review, we searched Medline, Medline In-Process and Other Non-Indexed Citations, Embase, Web of Science, and the Cochrane Library using terms relating to TT1 and succinylacetone with the following criteria: participants were newborn babies, the target condition was TT1, the index test was tandem mass spectrometry measurement of succinylacetone in dried blood spots, the reference standard was urine testing for succinylacetone/clinical detection. We included studies reporting test accuracy outcomes. One reviewer screened titles and abstracts, and assessed full text papers. A second reviewer examined 20% of these. Quality assessment (unadjusted Quality Assessment of Diagnostic Accuracy Studies tool; QUADAS) and data extraction were conducted by one reviewer. The systematic review included these differences: (1) broader search terms, (2) two reviewers independently screened titles and abstracts, and assessed full text papers, (3) quality assessment was conducted by two reviewers using an adjusted QUADAS, and (4) data extraction was conducted by one reviewer and checked by a second. A narrative synthesis was conducted. Results: Compared to the rapid review, the systematic review search identified four times as many potential items, ten extra papers for full assessment, and one additional paper for inclusion. Quality assessment in the rapid review resulted in more frequent ratings of 'unclear' risks of bias and applicability concerns. A misinterpretation in the rapid review data extraction was identified by the second reviewer in the systematic review. Conclusion: Benefits in terms of the reduction in time and resources required to conduct a rapid review may come at a cost of increased errors. Due the rarity of our target condition, the question against which we compared rapid- and systematic reviews resulted in a small number of potential studies. This may have limited the opportunities for difference to arise between the two approaches.